Здійснення органами ДПУ–НКВС України репресій проти Православної церкви на Одещині (1930-ті – 1940-ві рр.) - Михайлуца, М. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The are shown courts under clergy of Bessarabia, who took part in political parties of Rumania and also with those who cooperated with Rumanian orthodox ledation in Transnistria in 1941–1944 yy. The are some statistical information in the article.